Analisis Rasio Kinerja Keuangan Pada PT Indonesia Tobacco Tbk. - Sri_Muryani Cahyani; Titik Susilowati; Shollahudin Al Rafsanjani; Sri Hermuningsih (SMARTINDO, 2025)
This study was conducted to analyze the financial statements of PT Indonesian Tobacco Tbk by analyzing the liquidity ratio (current ratio and quick ratio), activity ratio (accounts receivable turnover ratio, inventory turnover ratio, fixed asset turnover ratio and total asset turnover ratio), debt ratio (debt to asset ratio, time earned) and profitability ratio (profit margin, return on equity, return on assets) by comparing using the financial statements of 2022 and 2023. The research method used is a qualitative descriptive method, namely by collecting, processing, analyzing and presenting descriptive data from the financial statements of 2022 and 2023 of PT Indonesian Tobacco Tbk. The results of the study obtained from comparing the financial performance of PT Indonesian Tobacco Tbk in 2022 and 2023, the liquidity ratio decreased in 2023, but was still within the liquid criteria, able to pay off its short-term debt obligations, for the activity ratio it increased in 2023, for the debt ratio it showed that the company was getting healthier, while for the profitability ratio it decreased in 2023 but was still able to produce high value.